Nearshore Dissolved and Particulate Organic Matter Dynamics in the Southwestern Baltic Sea: Environmental Drivers and Time Series Analysis (2010–2020) - Osterholz, Helena; Burmeister, Christian; Busch, Susanne; Dierken, Madleen; Frazão, Helena C.; Hansen, Regina; Jeschek, Jenny; Kremp, Anke; Kreuzer, Lars; Sadkowiak, Birgit; Waniek, Joanna J.; Schulz-Bull, Detlef E. (Frontiers in Marine Science, 2021)
Dissolved and particulate organic carbon (DOC, POC) and nitrogen (DON, PON) constitute essential nutrient and energy sources to heterotrophic microbes in aquatic systems. Especially in the shallow coastal ocean, the concentrations are highly variable on short timescales, and cycling is heavily affected by different sources and environmental drivers. We analyzed surface water organic carbon and nitrogen concentrations determined weekly from 2010 to 2020 in the nearshore southwestern Baltic Sea (Heiligendamm, Germany) in relation to physical, chemical and biological parameters available since 1988. Mixing of low-DOC North Sea water with high-DOC Baltic Sea water, as well as in situ primary production, were confirmed as the main drivers of organic carbon and nitrogen concentrations. Tight coupling between POC, PON, chlorophyll a and phytoplankton carbon with DON seasonal dynamics corroborated the close relationship between phytoplankton production and degradation of organic nutrients with preferential remineralization of nitrogen. Significant changes in air and water temperature, salinity, and inorganic nutrients over time indicated effects of climate change and improved water quality management in the eutrophic Baltic Sea. Bulk organic nutrient concentrations did not change over time, while the salinity-corrected fraction of the DOC increased by about 0.6 μmol L–1yr–1. Concurrently, chlorophyll a and Bacillariophyceae and Cryptophyceae carbon increased, denoting a potential link to primary productivity. The high variability of the shallow system exacerbates the detection of trends, but our results emphasize the value of these extended samplings to understand coupled biogeochemical cycling of organic matter fractions and to detect trends in these important carbon reservoirs.